A review of interactive technologies supporting universal design practice - Zitkus, Emilene [UNESP] (Springer Nature, 2017)
This paper examines a range of user-centred interactive techniques that have been proposed by experts to overcome universal accessibility issues during design development. These tools are presented and analysed according to the compatibility with design practice. The paper contributes to a better understanding of the state of art regarding interactive tools for universal design and indicates areas for further development for the benefit of universal products and services.
Keywords: Design for all; Design process; Design tools; Inclusive design; Product development; Simulation tools